Acinemas : Lyotard's philosophy of film - Jones, Graham (Lecturer in media, communications and writing); Woodward, Ashley (Edinburgh University Press, 2017)
This collection presents, for the first time in English, all of Lyotard's major essays on film, an introductory essay by the leading French scholar on Lyotard's film-philosophy, an overview of Lyotard's practical film projects written by his collaborators, and a selection of critical essays by philosophers and film theorists.
Keywords: Lyotard, Jean-François, -- 1924-1998.; Lyotard, Jean-François, -- 1924-1998; Motion pictures -- Philosophy.; Motion pictures -- Aesthetics.; Painting and motion pictures.; Cinéma -- Esthétique.; Peinture et cinéma.; Cinéma -- Philosophie.; PHILOSOPHY -- History & Surveys -- Modern.; PHILOSOPHY -- Political.; Motion pictures -- Aesthetics; Motion pictures -- Philosophy; Painting and motion pictures